Prevalence and associated factor with frailty syndrome in the Brazilian elderly attended in primary care facilities: a cross-sectional study - Feitosa, Ankilma do Nascimento Andrade; Lacerda, Sheylla Nadjane Batista; Assis, Elisangela Vilar de; Abreu, Luiz Carlos de; Figueiredo, Francisco Winter dos Santos; Fonseca, Fernando Luiz Affonso; Adami, Fernando (ABCS Health Sciences, 2020)
Introduction: Frailty is a multidimensional syndrome that increases the vulnerability in the elderly, decreasing physiological reserves, intensifying the functional decline, being associated with numerous physical changes, determining greater risks to the elderly’s health. Objective: To analyze the association between frailty and sociodemographic conditions of the elderly met in primary care facilities in the city of Cajazeiras, northeastern Brazil. Methods: A cross-sectional study, conducted in July 2015, with 823 elderly people through semi-structured questionnaire containing the proposed frailty criteria by Linda Fried and colleagues, and analyzed using SPSS version 21. The Chi-Square test was used to assess the association between variables, considering p<0.05 as statistically significant. The sociodemographic data were collected using an instrument created by the authors. Results: The prevalence of frailty was 23.8% and is associated with older age groups (70-90 years) and older people who did not attend school (25.5%), and the main criterion of frailty found among the elderly was "slow walk" (71.7%). Conclusion: The frailty in elderly from Northeastern Brazil is associated with higher age and illiteracy.